2013
DOI: 10.7196/ajhpe.203
|View full text |Cite
|
Sign up to set email alerts
|

A model for community physiotherapy from the perspective of newly graduated physiotherapists as a guide to curriculum revision

Abstract: Background. Limitations in physiotherapy curricula have been reported. Work-based experiences, especially during compulsory community service, could inform curricula. Objective. To develop a model of community service physiotherapy to guide curriculum reform. Methods. In this appreciative inquiry, trained physiotherapy students conducted tele-interviews with newly graduated physiotherapists. Twelve recently graduated community-service physiotherapists -heterogeneous in gender, mother tongue, university attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 15 publications
(25 reference statements)
1
39
0
Order By: Relevance
“…[2,4,6] The students stated that being proficient in isiXhosa would have helped in HBR to minimise the verbal communication barrier. They reported that an introductory isiXhosa course in their 1st year seemed irrelevant to them at the time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[2,4,6] The students stated that being proficient in isiXhosa would have helped in HBR to minimise the verbal communication barrier. They reported that an introductory isiXhosa course in their 1st year seemed irrelevant to them at the time.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] These communities are often situated in under-resourced areas. Experiencing the real-life context of clients is vital for students so that they will ultimately provide effective interventions and develop social responsibility.…”
mentioning
confidence: 99%
See 3 more Smart Citations